(π‐Allyl)Pd Complexes Containing N‐Heterocyclic Carbene and Pseudohalogen Ligands – Synthesis, Reactivity toward Organic Isothiocyanates and Isocyanides, and Their Catalytic Activity in Suzuki–Miyaura Cross‐Couplings. Issue 28 (31st July 2013) - Kim, Hyun‐Kyung; Lee, Jung‐Hyun; Kim, Yong‐Joo; Nu Zheng, Zhen; Lee, Soon W.
Abstract: Dinuclear (π‐allyl)palladium chlorides, [(π‐allyl)Pd(μ‐Cl)]2, were cleaved by N‐heterocyclic carbenes (NHCs) to give mononuclear (π‐allyl)palladium–NHC chlorides, [(π‐allyl)Pd(Cl)(NHC)] (1 –6 ) [NHC = 1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene (IPR), 1, 3‐bis(2, 6‐diisopropylphenyl)‐4, 5‐dihydroimidazol‐2‐ylidine (SIPR), 1, 3‐bis(2, 4, 6‐trimethylphenyl)imidazol‐2‐ylidene (IMes)]. Complexes1 –6 were subsequently treated with aqueous NaN3, KSCN, KOCN, and CF3 COOAg to produce the corresponding mononuclear (π‐allyl)palladium–NHC pseudohalogen complexes, [(π‐allyl)Pd(X)(NHC)] (X = N3, NCS, SCN, NCO, CF3 COO) (7 –30 ). These products could also be obtained by treating dinuclear pseudohalogen‐bridged Pd complexes, [(π‐allyl)Pd(μ‐X)]2, which were prepared by replacing the μ‐Cl ligand in [(π‐allyl)Pd(μ‐Cl)]2, with aqueous NaN3, KSCN, KOCN, or CF3 COOAg, followed by cleavage with the NHCs. Reactions of [(π‐allyl)Pd(N3 )(NHC)] with organic isothiocyanates (R–NCS) or CH3 O(CO)C≡CO(CO)CH3 resulted in selective 1, 3‐dipolar cycloaddition into the Pd–azido bond to give heterocyclic compounds. By contrast, analogous reactions of [(η 3 ‐allyl)Pd(N3 )(IPr)] with an organic isocyanide (R–NC: R = tert ‐butyl, benzyl) gave the adduct [(η 3 ‐allyl)Pd(N3 )(IPr)]· (R–NC) as the only product or a mixture of the adduct and a dipolar cycloaddition product, [(η 3 ‐allyl)Pd{CN4 (R)}(IPr)], depending on the isocyanides used. Finally, a series of (π‐allyl)Pd–NHC pseudohalogen complexes, [(π‐allyl)Pd(X)(NHC)], exhibited high catalytic activity in Suzuki–Miyaura cross‐coupling reactions of aryl chlorides with arylboronic acids. Abstract : A series of (π‐allyl)palladium complexes containing N‐heterocyclic carbene and pseudohalogen ligands are prepared and their reactivity toward organic isothiocyanates and isocyanides is studied. Suzuki–Miyaura cross‐coupling reactions of aryl chlorides with aryl boronic acid catalyzed by these (π‐allyl)palladium complexes are reported.